The Cyclical Variation of Wage Premiums in the Canadian Manufacturing Industries - Milne, William; Ross, Thomas (Relations industrielles / Industrial Relations, 1984)
The Cyclical Variation of Wage Premiums in the Canadian Manufacturing Industries